Fractal dimension for bending–torsion fatigue fracture characterisation - Macek, Wojciech; Branco, Ricardo; Korpyś, Mateusz; Łagoda, Tadeusz (Measurement : journal of the International Measurement Confederation, 2021)
•Fractal dimension for fatigued samples of aluminium and steel alloys was investigated.•Correlation between fractal dimension and loading type was studied via entire fracture area method.•Average values of the fractal dimension exhibited fixed behaviour regardless of the material type.•Fractal dimension based on extreme values effectively correlated data using linear functions. Fracture surfaces after biaxial fatigue tests were compared using fractal dimension for three types of metallic materials in smooth and notched specimens made of S355J2 and 10HNAP steels and 2017-T4 aluminium alloy, considering both proportional and nonproportional cyclic loading. High-resolution optical 3D measurement studies were performed on the entire fracture surface. A direct correlation between fractal dimension and fatigue loading was established. This systematic relationship can serve as a basis for obtaining information about fatigue loading from the fracture surfaces of failed materials and structures. Moreover, measurements of the fracture surface with an optical profilometer, quantitative analysis, and fractography contribute to a better comprehension of the fatigue failure processes. Differences in individual zones of fatigue fractures were identified while demonstrating the correctness of the total fracture surface method.